2009
DOI: 10.1007/s12031-009-9181-z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anti-Parkinsonian Agent, Zonisamide, Attenuates MPTP-Induced Neurotoxicity in Mice

Abstract: Zonisamide, an anti-convulsant drug, has recently been shown to exert beneficial effects in Parkinson's disease (PD). However, actual pathophysiological mechanism underlying the anti-parkinsonian effect of zonisamide remains uncertain. Here we tested exactly the neuroprotective effect of zonisamide against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) neurotoxicity in mice. We observed that zonisamide attenuated MPTP-induced dopamine, 3,4-dihydroxyphenylacetic acid (DOPAC), and homovanillic acid (HVA) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…It was especially reported that MPTP induces the degeneration of spinal cord in a mouse model of MPTP intoxication (Samantaray et al, 2008). Pharmaceutical studies have been conducted using these animal models of PD-like neuropathological features as well as using actual PD patients (Dutta et al, 2008;Etminan et al, 2003;Hamaue 2000;Kasture et al, 2009;Liang et al, 2007;Neef and van Laar, 1999;Yano et al, 2009). However, these studies have not yet led to the development of satisfactory anti-parkinsonism drugs with longterm therapeutic effects for PD patients; for example, long-term treatment with Levodopa (a drug used to treat PD) is known to cause serious side effects such as dyskinesia (Calon et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It was especially reported that MPTP induces the degeneration of spinal cord in a mouse model of MPTP intoxication (Samantaray et al, 2008). Pharmaceutical studies have been conducted using these animal models of PD-like neuropathological features as well as using actual PD patients (Dutta et al, 2008;Etminan et al, 2003;Hamaue 2000;Kasture et al, 2009;Liang et al, 2007;Neef and van Laar, 1999;Yano et al, 2009). However, these studies have not yet led to the development of satisfactory anti-parkinsonism drugs with longterm therapeutic effects for PD patients; for example, long-term treatment with Levodopa (a drug used to treat PD) is known to cause serious side effects such as dyskinesia (Calon et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The dopaminergic mechanisms are dopamine release induction [14,15] and MAO-B inhibition [16]. The non-dopaminergic mechanisms are calcium channel blocker [13] glutamate [17], GABA [18] modulation, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier article reported that acute administration of ZNS (20 and 50 mg/kg) in rats increased intracellular and extracellular levels of dopamine and its metabolites in the striatum through inhibition of monoamine oxidase type B (MAO-B) activity [9]. Alternatively, ZNS has been reported to increase the activity and expression of tyrosine hydroxylase (TH) [10], and stimulate dopamine release in the rat striatum [9]. ZNS may improve motor impairments of Parkinson’s disease by its multiple effects on dopamine release and synthesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, experiments using neurotoxin-based mouse models have provided insights into the protective effects of ZNS against neuronal death. In MPTP-treated mice, intraperitoneal administration of ZNS (20 mg/kg) mitigated loss of nigral TH-positive neurons with attenuating dopamine depletion in the striatum [10]. In mice that received 6-OHDA to induce hemiparkinsonism, repeated intraperitoneal injection of ZNS (30 mg/kg) for 7 days also abrogated the reduction in nigral dopamine neurons [12].…”
Section: Introductionmentioning
confidence: 99%